Factores de riesgo laborales del personal profesional de Enfermería del Hospital General Julius Doepfner - Zona 7, Periodo Abril - Septiembre 2022 - Guamán Chalan, Judy Yadira (2023)
Occupational risks are physical, psychological, chemical, biological, ergonomic factors that affect the physical/mental health of the individual where their presence leads to the development of accidents and occupational diseases. For the execution of the research, the general objective was set: Identify the factors of occupational risk in the professional nursing staff of the Julius Doepfner General Hospital. The research was quantitative, descriptive, nonexperimental, cross-sectional, the universe was made up of 40 nursing professionals, with a sample of 36 participants in a non-probabilistic way, taking into account the staff who were on work hours and excluding the staff on vacation or maternity leave. The survey technique was used and a questionnaire, prepared by the author, was used as an instrument. The results found that nursing staff have a high level of exposure to biological risks, highlighting contact with contaminated material at 61.1% and body fluids at 77.8%. In chemical risks, professionals are exposed to anesthetic gases of 55.6% and povidone iodine of 63.9%, in physical-mechanical risks, personnel have never suffered falls from manipulating objects, this is 80.6%, but they manipulate instruments. sharps 83.3%; In ergonomic risks, 47.2% of respondents are exposed to the handling of loads; and when performing forced postures 41.7%; Finally, in psychosocial risks, participants expressed working under pressure in 61.1%, and having suffered aggression/mistreatment by colleagues/patients in 58.3%. It is concluded that nursing staff are exposed to different occupational risks, increasing the possibility of suffering accidents, affecting their work performance and lifestyle